A hydrogel-driven microfluidic suction pump with a high flow rate. Issue 10 (9th April 2019) - Seo, Jaedeok; Wang, Cong; Chang, Sooyoung; Park, Jungyul; Kim, Wonjung
Abstract : A portable, non-powered, long-term working microfluidic suction pump driven by a superabsorbent polymer was developed. Abstract : We propose a portable, non-powered, long-term working suction pump with a high flow rate for microfluidic devices. The pump is driven by a superabsorbent polymer enclosed in a housing with porous fins to accelerate water absorption. We experimentally demonstrate that the pump creates an outstanding flow rate of more than 80 μl min −1 and an absorption volume of ∼20 ml. We address the key design principles underlying the outstanding performance of the pump. As an exemplary application, we constructed a portable power generator by combining the hydrogel pump with a reverse electrodialysis (RED) device. This portable system, powered only by KCl solutions with different ion concentrations, exhibited an output density of ∼70 μW cm −2 for more than an hour. The proposed versatile hydrogel pump could provide a breakthrough for developing various portable microfluidic systems.